Culture-related semantic losses in English translations of travel guides - Chen, Shiyue (2024)
Amidst China’s focus on cultural export and the backdrop of economic globalization, the tourism sector emerges as a strategic channel for cultural dissemination. Translating Chinese culture-specific items in travel guides becomes pivotal in bridging the gaps between different cultures and facilitating cross-cultural understanding. Despite the growing demand for accurate translation, tourism translation faces criticism for struggling to preserve intricate cultural connotations and contextual elements from the source text. A lack of research exists to address cultural connotation losses and their implications for semantic accuracy in translating Chinese culture-specific items into English. This research aims to address this gap and investigates culturally related semantic losses in the English translation of Chinese travel guides published by Lonely Planet, focusing on the destinations of Beijing, Shanghai, and Sichuan. It aims to achieve the following: 1) the types of cultural connotation losses in the English translation of Chinese culture-specific items in Lonely Planet’s travel guides; 2) the culturally related semantic losses, with particular reference to cultural connotations losses that result in partial or complete semantic losses; 3) the macro-level translation method of the identified micro-level translation procedures impact on the culturally related semantic losses; and 4) the factors that caused these culturally related semantic losses. The current research adopts a qualitative-descriptive approach, with strategic inclusion of percentage numbers to reinforce qualitative findings. This inclusion serves to quantitatively reinforce key observations and enhance the robustness of the research. The analysis focuses on 500 collected culture-specific items in their Englishtranslated versions, employing Nababan et al.’s (2012) translation quality assessment, Venuti’s (1995) domestication and foreignisation, and Baker’s (1992) typology of losses. The data were purposefully sampled using maximum variation sampling to address the research questions, followed by content analysis. The findings identified seven types of cultural connotations losses. Specifically, these pertained to historical background, rhetorical devices, religious information, local customs, cuisine, poetry and literary works, and architectural features. In addition, certain cultural connotations loss resulted in both partial and complete semantic losses, with partial semantic loss being dominant. Moreover, the findings uncovered the prevalence of macro-level translation method foreignization, indicating a prioritisation by the translators in preserving the cultural elements of the source text. Within the micro-level translation procedures, meanwhile, literal translation, transliteration, and literal translation plus transliteration were found to be the dominant modes. Factors contributing to culturally related semantic losses were also evaluated, such as semantic complexity, differences in meaning, lack of lexicalization, and the translators’ inappropriate choice of equivalents. The present study is significant within translation studies because it illuminates the distinctive types of cultural connotations losses generated by translating culturespecific items, with reference to the travel guides. The findings offer valuable insights for translators and researchers, enhancing understanding of the intricacies of translating cultural connotations. The comprehensive typology developed in this study can inform future translation practice and lay the groundwork for further research. Finally, the present study emphasises the importance of cultural accuracy and linguistic richness, contributing to the ongoing development of cross-cultural communication.